PRESERVING THE STATUS QUO IN DAVID FRANKEL'STHE DEVIL WEARS PRADA: A MARXIST PERSPECTIVE - Suheni, Suheni (2011)
The major problem of this study is how preserving status and power is very important in our life. Hence, the focus of this research is the major principle of Marxism. In analyzing The Devil Wears Prada, the writer uses qualitative method. The object of the study is David Frankel's The Devil Wears Prada produced by twentieth Century Fox. The primary data source is the movie itself, while the secondary data source is the other sources related to analysis such as script, books, and movie review. The technique of the data collection is note taking and scene capturing. The study comes to the following conclusions. Firstly, based on the structural analysis, it is clear that this movie, David Frankel suggests the idea that power, status, positions can not makes someone get happiness. Secondly, based on the Marxist analysis, it is evident that in order to cope with materialism one uses any kinds of way to make one gets prosperity, status, and power.